Communication Barriers Faced by Ustaz Guides of KBIHU Al Waritsah with Indonesian Hajj Pilgrims - Faisyal Muhammad Syahri Alwi; Diah Fatma Sjoraida; Hadi Suprapto Arifin (Jurnal Komunikasi, 2025)
Effective communication between Hajj guides (ustaz pembimbing) and pilgrims is a key factor in ensuring the success of Hajj guidance services in Indonesia. In practice, however, communication barriers often disrupt interactions, reduce service effectiveness, and weaken interpersonal trust. This study aims to identify and analyze the communication barriers faced by the guides of Kelompok Bimbingan Ibadah Haji dan Umrah (KBIHU) Al Waritsah, Group 16, Bandung City, during the 2024 Hajj season. The analysis draws on the perspective of interpersonal communication and the concept of communication barriers, considering affective, structural, relational, cultural, and perceptual/intrapersonal dimensions. The uniqueness of this case lies in three specific conditions shaping the communication dynamics: the absence of the KBIHU leader for the first time, the sudden onset of dementia symptoms in an elderly pilgrim that the KBIHU had never previously handled, and the presence of a pilgrim from the Persatuan Islam (Persis) organization within a KBIHU affiliated with Nahdlatul Ulama (NU). This study employed a qualitative case study approach, conducting in-depth interviews with three guides and eight pilgrims representing diverse ages and educational backgrounds. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal five main categories of communication barriers: (1) affective barriers involving negative emotions and complaints, (2) structural-hierarchical barriers related to social status distance, (3) relational barriers stemming from unmet role expectations, (4) cultural and ideological barriers due to differences in religious affiliation, and (5) perceptual and intrapersonal barriers involving prejudice and internal conflict. These findings provide valuable insights for developing more empathetic, open, and adaptive communication strategies for Hajj guides, and offer practical recommendations for KBIHU and the Ministry of Religious Affairs in designing training programs, emergency response protocols, and inclusive guidance models that address the diverse backgrounds of pilgrims.